The implementation of human trafficking laws in Bangladesh: comparison with Malaysia / Che Audah Hassan, Maruf Billah and Fuad Mahbub - Hassan, Che Audah; Billah, Maruf; Mahbub, Fuad (Universiti Teknologi Mara Cawangan Pulau Pinang, 2024)
Human trafficking is an insensitive attack on the dignity and liberty of human beings. Millions of people worldwide are becoming victims of human trafficking every year. Bangladesh has become one of the most victim-supplied countries in the Middle East, Asia, Africa, and Europe. Therefore, to prevent human trafficking the government of Bangladesh has introduced several laws, nevertheless, it has yet to achieve the objective effectively. This study adopts a qualitative research methodology, utilizing secondary data sources like academic publications, legal documents, and international reports to assess the efficacy and constraints of human trafficking legislation in Bangladesh and Malaysia. A comparative analysis considers the strengths and limitations of the legal systems of both nations, offering recommendations for enhancing Bangladesh's enforcement mechanisms informed by Malaysia's successful practices. Hence, in implementing human trafficking laws to combat human trafficking in Bangladesh, this study first examines the existing legal frameworks of Bangladesh on combatting the offense of human trafficking. Secondly, it explores the ineffectiveness of the existing legal frameworks that are not implemented accordingly. Third, it examines the Malaysian anti-trafficking laws and their applications in the Malaysian jurisdiction, since Malaysia is one of the best destinations for Bangladeshi traffickers to deploy the victims of human trafficking. Lastly, based on the lessons from Malaysia, this study concludes by suggesting several recommendations to the Bangladesh government such as increasing severe sentences for corrupted public officers involved in human trafficking, providing effective training to the police officers, prosecutors, and judges in dealing with human trafficking cases, enhancing collaboration with other countries in cross-border trafficking and providing more facilities to support the protection of the victims of trafficking.